Introduction to Psychology and Leadership. Leadership Management Course Course Development Model for Phase I. - Westinghouse Learning Corp., Annapolis, MD.; Westinghouse Learning Corp., Annapolis, MD.; Naval Academy, Annapolis, MD. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
The course development model used in the development of the leadership course for the United States Naval Academy by the Westinghouse Learning Corporation is briefly presented and examined, with those features which are specific to the USNA indicated. The final report of the project is under EM 010 418, EM 010 419, and EM 010 484. EM 010 418 through EM 010 447 and EM 010 451 through EM 010 512 are related reports. (Author/RH)
Sponsoring Agency: National Center for Educational Research and Development (DHEW/OE), Washington, DC.
Contract Number: N00600-68-C-1525.
ERIC Note: See also EM 010 418 and EM 010 419.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Education; Autoinstructional Aids; Communication (Thought Transfer); Course Content; Curriculum Design; Curriculum Development; Individual Psychology; Individualized Instruction; Instructional Design; Leadership; Leadership Training; Military Training; Multimedia Instruction; Psychology; Research Reports; Social Psychology